2021
DOI: 10.3390/polym13244277
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microplastics Released Based on Polyester Fabric Construction during Washing and Drying

Abstract: With the increasing production of synthetic materials, more microplastic fibers are being generated while washing clothes. Consequently, these particles are increasingly detected in the aquatic environment. Synthetic fibers produced via washing have a relatively high contribution to microplastic pollution. Hence, recent research on reducing the release of microplastic fibers is attracting considerable attention. In this study, fabric-specific analysis was performed by strictly controlling various factors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
(23 reference statements)
0
9
0
4
Order By: Relevance
“…Additionally, many studies have provided estimates of microfiber emissions from synthetic textiles during machine washing. Numerous studies and results show that textiles are among the main potential polluters due to the release of fibres, and that one of the reasons for this is the washing process [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Research has shown that the type of construction itself affects the amount of microfibers released.…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many studies have provided estimates of microfiber emissions from synthetic textiles during machine washing. Numerous studies and results show that textiles are among the main potential polluters due to the release of fibres, and that one of the reasons for this is the washing process [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Research has shown that the type of construction itself affects the amount of microfibers released.…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…The first wash releases most of the microfibers, and as the number of washes increases, the release will decrease. It is emphasized that washing parameters such as time and temperature have an influence on the release of microfibers [ 44 ]. Some possibilities to avoid this phenomenon are listed in Table 2 .…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…The wastewater, collected in 20 L containers for each washing procedure, was filtered separately. A specific filtration method reported by Choi et al [20] was used. The weight and length of the microplastics were also analyzed.…”
Section: Filtration and Analysismentioning
confidence: 99%
“…De acordo com Kelly et al (2019), as maiores fontes de poluição microplástica incluem pneus de carros e vestuário de origem sintética, que podem entrar no ambiente através das águas residuais utilizadas nas lavagens domésticas desses tecidos. microplásticos (CHOI et al, 2021).…”
Section: Microplásticosunclassified
“…e) Uma maior densidade e compactação do tecido tende a liberar menos microplásticos (CHOI et al (2021). f) Os processos de secagem doméstica também liberam microplásticos, evidenciando um risco em potencial para os moradores da residência (CHOI et al, 2021) O 'BRIEN et al (2020).…”
Section: A Lavagem Doméstica De Artigos Do Vestuáriounclassified